Electric conductivity in epoxy matrix with nanoparticles - Włodarska, Magdalena; Partyka, Michał; Bąk, Grzegorz; Mossety-Leszczak, Beata; Galina, Henryk; Florjańczyk, Zbigniew; Łokaj, Krzysztof (Wydawnictwo Politechniki Łódzkiej, 2012)
This work presents results of DC conductivity measurements obtained for epoxy matrices with different concentration of the nanofiller. In the first step, optimal curing conditions were determined - which turned out to be similar to those established for a plain epoxy matrix. In order to confirm stability of the matrix, measurements of the current-time dependency were made, which clearly show both the chemical and electric stabilization at the given temperature. All the obtained materials appeared to be good insulators with high activation energy. It was observed that the activation energy decreases slightly with increasing concentration of the nanofiller.

W pracy zaprezentowano wyniki pomiarów przewodnictwa stałoprądowego uzyskane dla matryc epoksydowych z różnym stężeniem nanonapełniacza. Początkowo ustalono optymalne warunki sieciowania, które były podobne do tych ustalonych dla samej matrycy. W celu potwierdzenia stabilności matrycy przeprowadzono pomiary zależności prądu od czasu, które dobrze obrazują zarówno stabilizację chemiczną, jak i elektryczną w danej temperaturze. Wszystkie uzyskane materiały okazały się dobrymi izolatorami z dużą energią aktywacji. Zauważono, że wraz ze wzrostem stężenia nanocząstek energia aktywacji nieznacznie maleje.
Przewodnictwo elektryczne w matrycach epoksydowych z nanocząsteczkami